The Role of Natural Resources in Achieving Economic Growth: (A Comparative Study between the Japanese and Saudi Economies) for the Period 2000-2023 - Nahi Shaker , Ibtihal (Iraqi Journal for Administrative Sciences, 2026)
This study aims to analyze the relationship between natural resource scarcity and economic growth, using Japan as a case study and comparing it with a resource-rich country such as Saudi Arabia over the period 2000–2023. The research is based on the premise that the lack of natural resources does not necessarily hinder economic growth; rather, it can serve as a stimulus for innovation, economic diversification, and technological advancement when accompanied by effective policies in education, research, and trade openness. Data were drawn from the World Bank (WDI) and the OECD, covering key variables including real GDP growth, natural resource dependency, public expenditure on education, R&D spending, and trade openness. The findings reveal that Japan has successfully transformed its resource scarcity into a competitive advantage by investing heavily in human capital and technological innovation. Conversely, Saudi Arabia shows a pattern of high dependency on oil revenues, with growth fluctuations linked to global energy price cycles. The study concludes that effective management of scarcity can promote sustainable growth, whereas poorly managed resource abundance may result in structural imbalances, commonly described as the “resource curse.